WORKING RESOURCE INCREASE OF THE WEAR-RESISTANT CHROMIC CAST IRONS PARTS OF EQUIPMENT ON PRODUCTION OF BRICK OF CLAY AND CENTRIFUGAL GRINDERS - K. E. Baranovsky; V. M. Ilushenko; E. F. Baranovsky; G. P. Korotkin (Литьë и металлургия)
The ways of working resource increase of the wear-resistant chromic cast irons details of equipment on production of brick of clay and centrifugal grinders are examined. The experimental wear-resistant cast iron as substitute of IChH28N2 is offered.